Upaya peningkatan kemampuan perkalian tingkat dasar melalui permainan congklak matika - Rohaniah, Siti Maspuroh; Wibowo, Eko Wahyu; Rachmiati, Wida (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
This research was motivated by the low basic multiplication ability at MI Tarbiyatul Mubtadiin. This is due to the lack of learning media and learning is also dominated by the teacher. So student activities are limited which results in low ability in basic multiplication. Therefore, this research was conducted to improve the ability in multiplication at the basic level using the Congklak-matika game media with a sample of 8 students. This research method uses Classroom Action Research (CAR) which is carried out in two cycles. Each cycle has four phases consisting of planning, action, observation, and reflection. Data collection techniques in the form of tests and observations and interviews. The results showed that the students' multiplication ability increased in each cycle. The increase was based on the acquisition of students' numeracy test results. this is evidenced in the first cycle the students' multiplication ability, which is 37.5%, is categorized as lacking and in the second cycle, the students' multiplication ability, which is 87.5%, is categorized as good and it is stated that the basic level multiplication learning through the congklak-matika game has reached the minimum completeness criteria or is declared successful. Therefore, the results of this study prove that the application of the Congklak-matika game media is able to improve students' abilities in mathematics subjects in the basic multiplication material for class 3 MI Tarbiyatul Mubtadiin so that the Congklak-matika game can be used as a learning medium